2023
DOI: 10.1039/d2fo03531f
|View full text |Cite|
|
Sign up to set email alerts
|

Uncovering the effect of Moringa oleifera Lam. leaf addition to Fuzhuan Brick Tea on sensory properties, volatile profiles and anti-obesity activity

Abstract: As a nutritious plant with valuable potential, the Moringa oleifera Lam. leaves addition on Fuzhuan Brick Tea (FBT) for the co-fermentation was an industry innovation and a new route to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…The content of astragalin (3-O-glucoside kaempferol) (18), rutin, quercetin (19)(20)(21)(22), polysaccharide (23), and miRNA (24) in MO is known to be able to inhibit PPARγ based on in vitro and in vivo studies. Inhibition of PPARγ was also found when administering petroleum ether extract MO (20), CH2Cl2 extract MO (25), and a combination of MO and Fuzhuan Brick Tea which contains various phytochemical compounds such as α-linolenic acid, strictin, isovitexin, astragalin, catechin, epicatechin, epicatechin gallate, gallocatechin, epigallocatechin, epigallocatechin gallate and gallic acid (26,27). Inhibition of PPARγ explains the role of MO as an inhibitor of adipogenesis and improves insulin sensitivity.…”
Section: Mechanism Of Adipogenesis In Obesity and Pathway Of Inhibiti...mentioning
confidence: 95%
“…The content of astragalin (3-O-glucoside kaempferol) (18), rutin, quercetin (19)(20)(21)(22), polysaccharide (23), and miRNA (24) in MO is known to be able to inhibit PPARγ based on in vitro and in vivo studies. Inhibition of PPARγ was also found when administering petroleum ether extract MO (20), CH2Cl2 extract MO (25), and a combination of MO and Fuzhuan Brick Tea which contains various phytochemical compounds such as α-linolenic acid, strictin, isovitexin, astragalin, catechin, epicatechin, epicatechin gallate, gallocatechin, epigallocatechin, epigallocatechin gallate and gallic acid (26,27). Inhibition of PPARγ explains the role of MO as an inhibitor of adipogenesis and improves insulin sensitivity.…”
Section: Mechanism Of Adipogenesis In Obesity and Pathway Of Inhibiti...mentioning
confidence: 95%
“…By adding Moringa oleifera Lam. leaves to Fuzhuan brick tea (FBT) from PTB for co‐fermentation, the product had more alkaloids, amino acids, lipids, organic acids, quinate, and less polyphenols than FBT, which achieved a higher overall acceptance score, along with better anti‐lipids, antidiabetic, and anti‐inflammatory activities (Li et al., 2023). It is worth noting that although TPPs in PTB chelate metal ions to scavenge free radicals in vitro, such chelation may inhibit the absorption of minerals (by 90%) (Dueik et al., 2017).…”
Section: Value‐added Utilization Of Pruned Tea Biomass In the Food In...mentioning
confidence: 99%
“…At the same time, as the storage time of Fu brick tea goes on, especially the changes in storage environment condition factors, such as temperature, light, and humidity, will further affect the aroma characteristics of Fu brick tea, which will have a crucial impact on the production and consumption of Fu brick tea [ 4 ]. In this instance, co-fermenting Fu brick tea with mulberry leaves [ 5 ], moringa leaves [ 6 ], citrus peels [ 7 ], and other food and medicinal plants is not only an industrial invention but also a novel approach to successfully enhance the distinctive aroma of Fu brick tea.…”
Section: Introductionmentioning
confidence: 99%
“…The studies that have been conducted have shown that the fung flower aroma of Fu brick tea is composed of 1-octanol and 1-heptadecanol with stale aroma attributes, methyl salicylate, acetophenone, and benzyl alcohol with green aroma attributes, 2-pentylfuran with roast aroma attributes, and geranyl acetone and β-violets with floral and fruity aroma attributes [ 8 , 9 ]. It is worth noting that the addition of Moringa leaves during the production of Fu brick tea can effectively contribute to the increase in the contents of aldehydes, ketones, and alcohols, as well as endow Fu brick tea with a rich floral and fruity aroma and the sweetness attributes of compounds such as 2,6,6-trimethyl-1-cyclohexene-1-carboxaldehyde and 3-buten-2-one, whereas traditional Fu brick tea only has the fatty aroma attribute of (E)-2-octenal [ 6 , 10 ]. For example, the addition of citrus peel to pu-erh tea improves the flavour quality of pu-erh tea with the odour-active components in citrus peel, giving citrus pu-erh tea a unique and harmonious flavour [ 7 ].…”
Section: Introductionmentioning
confidence: 99%